Formulation Development And Evaluation Of Injection Of Poorly Soluble Drug Using Mixed Solvency Concept - R. K. MAHESHWARI; RAJENDRA SHILPKAR (International Journal of Pharma and Bio Sciences, 2012)
Mixed solvency, a new concept of solubilization states that all substances whether solids, liquids or gases possess solubilizing power and hence concentrated solution containing various dissolved substances in any liquid can also improve the solubility of poorly soluble drugs. Mixed solvency technique can be employed in injection formulation of poorly soluble drugs in order to reduce concentration of individual solubilizer (used for solubility enhancement) to minimize the toxic effects of solubilizers. For example in most of the methods of aqueous solubilization, high concentration of an additive (hydrotropic agent/cosolvents/surfactants/cyclodextrins etc.) is required to produce an appreciable increase in solubility of a poorly water soluble drug. In this case, the solubilizing agent employed to give a desirable solubility for the poorly soluble drug may produce its own toxicity. Similarly, the presence of several oil soluble additives (each in small concentration) in oil, forming a concentrated solution may enhance the oil solubility of a poorly oil soluble drug efficiently. In the present investigation, rifampicin was selected as model poorly oil soluble drug. Castor oil was used as model oil and thymol, menthol, camphor, phenol, ethanol, benzyl alcohol and oleic acid were used as model oil soluble/miscible addatives. Oily injection was made as a result of oily solubility effect of these additives. The results of solubility study revealed the significance of mixed solvency and the stability studies data supports that the developed formulation using this technique gives good stability also.